ANALYSIS OF THE STUDENTS’ MOTIVATION TO OBTAIN CLINICAL THINKING SKILLS AT THE DEPARTMENT OF PATHOLOGICAL PHYSIOLOGY - Сілкіна, Ю.В.; Колдунов, В.В.; Клопоцький, Г.А.; Хмель, С.І.; Козлова, Ю.В.; Бібікова, В.М.; Гузь, В.А. (World of Medicine and Biology, 2014)
To determine the index of the Pearson correlation between the results of the final module control and test control "Step 1". It was found that the level of motivation on the I Faculty of Medicine is the highest (IP = 0.74, p
Keywords: students; education; exam of pathophysiology; “Step 1”